Cyanus uysalii (Asteraceae, Cardueae), a new combination for the flora of Turkey - Negaresh, Kazem (Phytotaxa, 2020)
Cyanus uysalii (Şirin & Çeçen) Negaresh is proposed here as a new combination. It is morphologically similar to C. bourgaei, but differs from it by the stem length, the involucres size, the florets length, the rosette leaves dissection, and the achenes size.